PHYSICAL EDUCATION - A WAY TO REDUCE FAMILY BUDGET EXPENDITURES (ResearchJet Journal of Analysis and Inventions, 2021)
The article analyzes and substantiates the important tasks of physical education, its role and importance in reducing family budget expenditures. It also analyzes and draws conclusions on the need to focus on physical education in 100 family cases.